2021
DOI: 10.54489/ijcim.v1i1.47
|View full text |Cite
|
Sign up to set email alerts
|

The Universal Artificial Intelligence Efforts to Face Coronavirus COVID-19

Abstract: Artificial intelligence (AI) has already changed the world and has made an effective impact in a range of fields including industry, criminal law, health, national security, transport, nanotechnology, intelligent cities as well as issues such as algorithms and access to the data.  This paper shows how these technologies are a great asset to humans and are programmed to reduce human effort as much as possible. They tend to possess the capability to work in an automated fashion. Therefore, manual intervention is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…The literature review revealed that scholars proposed many definitions and theories for leadership. The word or the concept of leadership, quite understandably, is a wide and complex one liable to many interpretations [64] [65]. There are different grades and leadership, from the ordinary to the sublime, and the most lasting category or legacy and the leadership dealt in the note is of sublime and heroic level or historical or history creating [66] [67].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature review revealed that scholars proposed many definitions and theories for leadership. The word or the concept of leadership, quite understandably, is a wide and complex one liable to many interpretations [64] [65]. There are different grades and leadership, from the ordinary to the sublime, and the most lasting category or legacy and the leadership dealt in the note is of sublime and heroic level or historical or history creating [66] [67].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Digital Operations is the idea of blending corporate procedures with ease and automation to make operational models that please customers and boost performance. A firm's most crucial business activities are controlled, re-engineered [21], updated, and carried out through digital operations to reduce operational costs, enhance user experiences, offer better results, and achieve top-line growth [22]. A company can establish more practical operational models and achieve method excellence by creating automated, data-driven platforms and trade utilities.…”
Section: Digital Operationsmentioning
confidence: 99%
“…As cyberchondriacs seek professional medical help, they can also strengthen the trust and bond they have with their healthcare providers. Healing from constant worry and anxiety for cyberchondriacs is possible through the active desire to become better, and through family and friend support [41,42,43,44,45]…”
Section: Proposed Solutionmentioning
confidence: 99%
“…Leading research suggests that Cognitive Behavioral Therapy (CBT) is by far the most popular and effective therapeutic treatment option for people who suffer from cyberchondria [42,43,44,45,46]. Cognitive Behavioral Therapy involves a mixture of comprehensive psychological education and exposure therapy.…”
Section: Related Workmentioning
confidence: 99%